2016
DOI: 10.1186/s12870-016-0766-8
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of plant growth regulators and reactive oxygen species to regulate petal senescence in wallflowers (Erysimum linifolium)

Abstract: BackgroundIn many species floral senescence is coordinated by ethylene. Endogenous levels rise, and exogenous application accelerates senescence. Furthermore, floral senescence is often associated with increased reactive oxygen species, and is delayed by exogenously applied cytokinin. However, how these processes are linked remains largely unresolved. Erysimum linifolium (wallflower) provides an excellent model for understanding these interactions due to its easily staged flowers and close taxonomic relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 52 publications
3
13
0
Order By: Relevance
“…ROS levels tend to increase during senescence, but it is not yet clear how this is connected to developmental senescence (van Doorn and Woltering, 2008; Salleh et al , 2016). In hibiscus, transcripts encoding enzymes committed to ROS control were enriched (Supplementary Table S6).…”
Section: Resultsmentioning
confidence: 99%
“…ROS levels tend to increase during senescence, but it is not yet clear how this is connected to developmental senescence (van Doorn and Woltering, 2008; Salleh et al , 2016). In hibiscus, transcripts encoding enzymes committed to ROS control were enriched (Supplementary Table S6).…”
Section: Resultsmentioning
confidence: 99%
“…However, abiotic or biotic stresses often cause a serious imbalance in any cell compartment because of increasing ROS generation or decreasing antioxidative capacity [ 37 ]. Leaf senescence is accompanied by the accumulation of ROS in deteriorating tissues; meanwhile, a loss in activities of antioxidant enzymes occurs during the progression of senescence [ 38 ]. The increasing ROS accumulation in turn results in enhanced leaf senescence [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…It revealed that 499 up- and 96 down-regulated genes in total were identified in the ZjSGR -overexpressing plants, implying a preferential role of ZjSGR in regulating gene expression. SEN1, NYC1, SAG21, SAG14 , and SAG39 were selected as positive markers to monitor the senescence progress in plants (Jing et al, 2002; Ren et al, 2010; Zhou et al, 2011; Jibran et al, 2015; Salleh et al, 2016). The expression levels of all the senescence related DEGs in ZjSGR -overexpressing plants were proved to be up-regulated, implying that the accelerated senescence progress in the transgenic plants.…”
Section: Discussionmentioning
confidence: 99%